Diseño de una escuela utópica explorando las posibilidades de un ambiente educativo ideal en Guayaquil - Prias Mármol, Irina Valeska (2024)
In Guayaquil, the current educational institutions present a large number of problems in architectural and functional aspects that impede the good academic and recreational development of children. In view of this, the design of a utopian school, exploring the possibilities of an ideal educational environment, aims to improve the needs of safety, comfort and resource optimization of these facilities, integrating them into a green environment. This by means of ergonomically designed spaces adapted to the different age ranges and needs of the children, offering a particular teaching to each one of them, starting from kindergarten I to seventh grade. Likewise, the cohesion of play and recreational spaces with modular, functional, colorful furniture that allows the development of motor activities is taken into account. On the other hand, areas destined to stay and rest that provide relaxation comfort after learning hours. In the same way, the integration of green areas inside the classrooms and in internal and external spaces of the institution are part of the design that in addition to providing dynamism, provide connection with the environment. Finally, in relation to the optimization of resources, priority is given to cross ventilation through large intelligent windows that are regulated according to the climate, as well as the implementation of motion sensors that allow the use of ventilation or artificial equipment to be reduced. This makes the building more sustainable and functional.